Bibliometric analysis on quantifying urban sprawl in assessing a comprehensive meaning of sprawl: A review - Rosni, Nur Aulia; Mohd Noor, Norzailawati; Abdullah, Alias (Malaysian Institute of Planners, 2017)
After more than half century has passed, urban sprawl remains as one of the most important and unresolved matters in the urban development process. This paper adopts "Bibliometrics Analysis" technique, which is a statistical analysis of scientific publications to review the studies on urban sprawl from the year 1996 till 2015 in order to identify the fundamental issues and problem of urban sprawl. This method allows the researcher to review the literature of topic of interest critically, not only based on national and international networks but includes the multi-disciplinary fields of science and technology relating to urban planning. The publications on urban sprawl were retrieved from the two largest scientific databases namely Scopus and ScienceDirect. The sampling of publications was based on the "Most Cited Articles" indicator. The findings on urban sprawl issues and problems are presented in four categories, which are the lack of consensus in defining urban sprawl, unavailability of method to quantify urban sprawl, access to data and tools, and varying urban sprawl patterns based on area. The findings of this study provide the gap for future research on urban sprawl.